013 Primary care direct access coronary artery calcium (CAC) score – prognosis from a novel service. (5th May 2016) - Tan, J; Lewis, G; Townend, J; Holloway, B
Abstract : Introduction: "NICE guidelines 95: Chest pain of recent onset" states that in a clinically low risk patient, negative CAC study alone excludes obstructive coronary disease. We describe a novel service which allows primary care direct access referral for CT CAC, established at UHB in 2011. Our study aims to evaluate the prognostic value of a negative CT CAC within our centre. Methods: A retrospective search of the Radiology Information Solution (RIS) system was performed for all patients referred between October 2011 to December 2013. Each report was reviewed on RIS to determine negative studies. Only patients above 35 years who fit the criteria for low risk (<29%) were included. Scans were performed on a dual source CT scanner without prior premedication. Outcome data on major adverse cardiac events (MACE) from the negative studies were obtained via the patient's electronic records and Office of National Statistics. The follow-up period was 2–4 years. Results: 407 patients had CAC studies. 267 patients with a zero CAC score were included. There were no cases of coronary-related deaths, coronary revascularisation or hospitalisation secondary to acute coronary syndrome (ACS). 14/267 (4.9%) patients re-attended the hospital via emergency department with chest pain but had ACS ruled out. 3/267 (1.1%) deaths occurred with none attributed to cardiovascular disease. Conclusion: Our study suggests that a negative CAC score in a population referred directly from primary care for exclusion of significant coronary disease in line with NICE guidance 95 is associated with a low incidence of cardiovascular morbidity and mortality.